(untitled) (UNED Research Journal, 2018)
The Rock Pigeon, Columba livia, is rare in natural environments but extremely successful in urban areas all over the world. Management programs are important because it is considered a pest in many cities. Nevertheless, no appropriate evaluation of methods to estimate urban pigeon populations is available in the literature. We compared three methods: a) the frequently used Stratified grids; b) Point counts, i.e. total pigeon counts with a mechanic counter in sampling points with a 50m radius; and c) Panoramas, 360o panoramic photographs. In nine urban parks in central Costa Rica, we made 1350 counts in total and compared: coefficient of variation (to assess precision); accuracy; time counting or taking photographs in situ; time merging photographs, counting pigeons in photographs, or typing data; and advantages or disadvantages. The Panorama Method is cheap, precise, accurate, secure, fast and easy. It can be used as an indicator or to estimate the actual population.